The impact of compression and confinement in tumor growth and progression: emerging concepts in cancer mechanobiology - Allison McKenzie Johnson; Charles Froman-Glover; Akshitkumar Mistry; Akshitkumar Mistry; Kavitha Yaddanapudi; Kavitha Yaddanapudi; Kavitha Yaddanapudi; Joseph Chen; Joseph Chen (Frontiers in Materials)
Cancer is one of the deadliest diseases despite aggressive therapeutics. This is due in part to the evolving tumor microenvironment (TME), which provide tumor supportive cues that promote tumor adaptation and progression. Emerging studies highlight the significant role of the biophysical characteristics in the TME in modulating all aspects of cancer aggressive and spread. With the advance of bioengineering platforms, deeper investigations into the impact of these biophysical features on cancer progression are being conducted with a growing appreciation of the intratumoral compression that underlie many of the biophysical changes. Intratumoral compression emerges early in tumor development and increases in magnitude as the tumor rapidly expands against itself and its surrounding tissue. This stress has effects on both the cancer cells and biophysical aspects of the TME, including hypoxia, shear stress, extracellular matrix (ECM) remodeling, and substrate stiffness. This creates a physically dense, pro-malignant environment that can both promote metastatic phenotypes and spread but also present biophysical barriers for immune cell infiltration. This review will analyze the effect of compressive stress on the TME, cancer cells, and on confined migration of cancer and immune populations.